A Large-Scale Screening Responding Sporadic Epidemic of COVID-19 in China by an Integrated Health-Care System - Xuru He; Xizhuo Sun; Fangfang Gong; Wenhai Li; Jinchun Lin; Hanqun Lin; Guangyu Hu (International Journal of Integrated Care, 2022)
Introduction: In the post-pandemic period of COVID-19, the majority of cities in China try to balance the normalization of epidemic prevention and social-economic development. However, the appearance of asymptomatic infected patients poses threats to public health, which might be infectious without clinical symptoms and only be detected by testing approaches. Methods: Along with the appearance of one symptomatic case, a regional large-scale screening program was carried out in Shenzhen City charged by a regionally integrated healthcare system. After describing the screening program, a retrospective cross-sectional study for the screening outcome and efficacy was conducted. Discussion: According to the screening results, the asymptomatic case was infectious and their close contacts should be quarantined cautiously as the close contacts of symptomatic cases. Besides, after integrating medical resources in Luohu district of Shenzhen, the medical capability of Luohu district improved greatly which could be demonstrated in inspection and organization abilities in this screening program. Conclusion: The large-scale screening contributed to preventing epidemic transmission. In the post-pandemic period, regular surveillance of asymptomatic cases and rapid response capability for emergent screening program are both crucial for the prevention and control of COVID-19 epidemic. The integrated healthcare system coordinating regional medical institutions and optimizing regional medical recourse has advantages to address public health emergencies.